I-Insulin transfer to mitochondria - Camberos, Maria del Carmen (2014)
The aim of this study was to determine if insulin is transferred to mitoplasts by insulin-degrading enzyme (IDE).Hepatic mitochondria were isolated and controlled by electron microscopy. IDE was obtained from rats muscle by successive chromatography steps. Insulin accumulation in mitoplasts and outer membrane + intermembrane space (OM + IMS) was studied with (125)I-insulin. Mitochondrial insulin accumulation and degradation was assayed with Sephadex G50 chromatography, insulin antibody and 5 % TCA. Mitoplasts and OM + IMS were isolated with digitonin. Insulin accumulation was studied at 25 °C at different times, without or with IDE, Bacitracin, 2,4-dinitrophenol, apyrase or sodium succinate + adenosine diphosphate. Insulin accumulation in mitoplasts and OM + IMS after mitochondrial cross-linking was studied with electrophoresis in SDS-PAGE, immunoblots of IDE, insulin or TIM23 (inner mitochondrial transporter) and autoradiography.The studies showed that addition of IDE increased insulin transfer from OM + IMS to mitoplasts, and the insulin accumulation in mitoplast was IDE dependent. Bacitracin and 2,4-dinitrophenol decreased this transfer. The [Insulin-IDE] complex and [Mitoplasts] was studied as a bimolecular reaction following a second order reaction. The constant "k" (liter.mol⁻¹ s⁻¹) showed that IDE increased and Bacitracin or 2,4-dinitrophenol decreased the velocity of insulin transfer. SDS-PAGE and immunoblots studies showed bands and radioactivity coincident with IDE, insulin and TIM23. Non degraded insulin was demonstrated in immunoblot after IDE immunoprecipitation from mitoplasts. Confocal studies showed mitochondrial colocalization of IDE and insulin.The results showed that insulin at 25 °C were transferred from OM + IMS to mitoplasts by IDE or that the enzyme facilitates this transfer, and they reach the matrix together.